Analysis of the factors that influence the emotional fatigue of women who work in commercial companies - Tigrero Machuca, Rosa Emilia; Bastidas Jiménez, Marcelo Javier (Journal of business and entrepreneurial studie, 2026)
This research was based on analyzing the factors that influence emotional exhaustion in women working in commercial companies, considering its impact on well-being and job performance. This study is justified by the growing incidence of burnout in emotionally demanding environments, which can affect mental health and reduce productivity. The main objective is to identify the factors associated with emotional exhaustion and their relationship with the organizational climate. In addition, it seeks to determine how these elements affect the motivation and job satisfaction of female workers. The methodology used is quantitative and descriptive, based on the application of surveys and structured interviews to a sample of 660 people working in commercial companies. Variables such as workload, organizational support, and work-life balance were analyzed. The main results indicate that work overload, lack of recognition, and poor support from superiors are determining factors in the onset of emotional exhaustion. Likewise, it was observed that a positive organizational climate contributes to mitigating its effects.